GAG replenishment therapy for bladder pain syndrome/interstitial cystitis. Issue 2 (28th December 2018) - Wyndaele, Jean Jacques J; Riedl, Claus; Taneja, Rajesh; Lovász, Sándor; Ueda, Tomohiro; Cervigni, Mauro
Abstract : Aims: To present a rationale for the inclusion of urothelial coating dysfunction in the etipathogenesis of bladder pain syndrome/interstitial cystitis (BPS/IC) and the preclinical and clinical evidence in support of glycosaminoglycan (GAG) replenishment therapy in the treatment of BPS/IC, supplemented by the clinical experience of medical experts in the field and patient advocates attending a symposium on GAG replenishment at ESSIC'17, the annual Meeting of the International Society for the Study of Bladder Pain Syndrome, held in Budapest, Hungary in 2017. Results: The urothelial GAG layer has a primary role in providing a permeability barrier to prevent penetration of urinary toxins and pathogens into the bladder wall. Disruption of the GAG layer contributes to the development of BPS/IC. The evidence shows that replenishment of GAGs can restore the GAG layer in BPS/IC, reducing inflammation, pain, and other symptoms. Conclusions: Although data from large randomized controlled studies are limited, long clinical observation and the experience of clinicians and patients support the beneficial effects of intravesical GAG replenishment therapy for providing symptomatic relief for patients with BPS/IC.